Building Community Resilience to Coastal Disasters: A Case Study of Cyclone Sidr in Bangladesh 2007 - Pechdin, Watchara; Nghia, Bui Phan Quoc (Journal of Social Policy, Social Change and Development, 2023)
The devastating consequences of ineffective implementation of community-based disaster risk reduction plans in coastal areas can be nothing short of disastrous. In order to maximize the chances of success when facing such a catastrophe, understanding the measures adopted by coastal communities is an important part of increasing resilience and preparing for disasters. This study looks into the actions taken by the coastal areas of Bangladesh in response to the 2007 Cyclone Sidr. Utilizing a scope review of the events, we can analyze the underlying causes of loss, while also determining the critical challenges government organizations or relief organizations may be confronted with. Through our research, we aim to provide policy makers and practitioners with advice on how to better address the requirements of coastal communities during times of future crises.